Ultra‐long Near‐infrared Repeatable Photochemical Afterglow Mediated by Reversible Storage of Singlet Oxygen for Information Encryption. Issue 13 (15th February 2023) - Chen, Lei; Sun, Kuangshi; Hu, Donghao; Su, Xianlong; Guo, Linna; Yin, Jiamiao; Pei, Yuetian; Fan, Yiwei; Liu, Qian; Xu, Ming; Feng, Wei; Li, Fuyou
Abstract: Photochemical afterglow systems have drawn considerable attention in recent years due to their regulable photophysical properties and charming application potential. However, conventional photochemical afterglow suffered from its unrepeatability due to the consumption of energy cache units as afterglow photons are emitted. Here we report a novel strategy to realize repeatable photochemical afterglow (RPA) through the reversible storage of 1 O2 by 2‐pyridones. Near‐infrared afterglow with a lifetime over 10 s is achieved, and its initial intensity shows no significant reduction over 50 excitation cycles. A detailed mechanism study was conducted and confirmed the RPA is realized through the singlet oxygen‐sensitized fluorescence emission. Furthermore, the generality of this strategy is demonstrated and tunable afterglow lifetimes and colors are achieved by rational design. The developed RPA is further applied for attacker‐misleading information encryption, presenting a repeatable‐readout. Abstract : We demonstrated a general strategy to realize repeatable photochemical afterglow (RPA) based on the reversible storage of singlet oxygen. Ultra‐long near‐infrared afterglow was achieved via the singlet oxygen‐sensitized fluorescence approach, and its intensity shows no significant reduction over 50 excitation cycles. The RPA system was further applied for attacker‐misleading information encryption, presenting a repeatable read‐out.